Stress signaling in plants: a mitogen-activated protein kinase pathway is activated by cold and drought. - Jonak, C (1996)
Yeast and animals use mitogen-activated protein (MAP) kinase cascades to mediate stress and extracellular signals. We have tested whether MAP kinases are involved in mediating environmental stress responses in plants. Using specific peptide antibodies that were raised against different alfalfa MAP kinases, we found exclusive activation of p44MMK4 kinase in drought- and cold-treated plants. p44MMK4 kinase was transiently activated by these treatments and was correlated with a shift in the electrophoretic mobility of the p44MMK4 protein. Although transcript levels of the MMK4 gene accumulated after drought and cold treatment, no changes in p44MMK4 steady state protein levels were observed, indicating a posttranslational activation mechanism. Extreme temperatures, drought, and salt stress are considered to be different forms of osmotic stress. However, high salt concentrations or heat shock did not induce activation of p44MMK4, indicating the existence of distinct mechanisms to mediate different stresses in alfalfa. Stress adaptation in plants is mediated by abscisic acid (ABA)-dependent and ABA-independent processes. Although ABA rapidly induced the transcription of an ABA-inducible marker gene, MMK4 transcript levels did not increase and p44MMK4 kinase was not activated. These data indicate that the MMK4 kinase pathway mediates drought and cold signaling independently of ABA.